1986
DOI: 10.1080/02643298608252677
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and experimental case for a visual deficit in specific reading disability

Abstract: We present three lines of evidence indicating a low-level visual deficit in a large percentage of specifically-disabled readers. This research is presented within the theoretical framework of spatial frequency analysis, in particular, the framework of transient and sustained subsystems.a. Measures of visible-persistence duration as a function of spatial frequency in normal and specifically-disabled readers show that disabled readers have a different pattern of temporal processing across spatial frequencies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
196
1
5

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(208 citation statements)
references
References 136 publications
(141 reference statements)
6
196
1
5
Order By: Relevance
“…Some psychophysical studies have failed to con®rm that such visual de®cits are associated with dyslexia ( [20,21,61], see also, [17] for review). Nevertheless most experimental evidence is consistent with the hypothesis that the M (or transient) pathway is a locus of their subtle visual impairments (for reviews see [29,30,56]). …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Some psychophysical studies have failed to con®rm that such visual de®cits are associated with dyslexia ( [20,21,61], see also, [17] for review). Nevertheless most experimental evidence is consistent with the hypothesis that the M (or transient) pathway is a locus of their subtle visual impairments (for reviews see [29,30,56]). …”
Section: Introductionsupporting
confidence: 58%
“…[54]). Although de®cits in component language skills such as phonological awareness are recognised as important causes of poor reading [8,49,55], there is now a large amount of literature showing that de®cient visual processing skills are also associated with reading diculties (see [29,30,32,46,56] for review). In the laboratory, many developmental dyslexics are found to be less sensitive than controls to dynamic visual stimuli, especially those of low contrast, low luminance, low spatial frequencies, and high temporal frequencies [10,28,30,31,33±35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the transient system theory has some empirical support (Breitmeyer, 1989;Badcock & Lovegrove, 1981;Lehmkuhle, Garzia, Turner, Hash, & Baro, 1993;Lovegrove et al, 1986;Lovegrove, Garzia, & Nicholson, 1990;Martin & Lovegrove, 1984), as does the motion perception theory (Eden et al, 1996). Thus, both warrant further comment.…”
Section: Visual Deficitsmentioning
confidence: 94%
“…Thus, Lovegrove and his associates have shown that poor and normal readers process high and low spatial frequency grids differently. They also have different contrast sensitivity functions, such that the poor readers require greater luminosity than the normal readers for distinguishing low frequency grids (Badcock & Lovegrove, 1981;Lovegrove et al, 1986Lovegrove et al, , 1990Martin & Lovegrove, 1984). That dyslexics are subject to trace persistence has been inferred from such findings.…”
Section: Visual Deficitsmentioning
confidence: 99%
“…An irregular magnocellular system could reduce the visual sensitivity for moving or flickering stimuli (Cornelissen et al, 1998a) and therefore to interfere with lexical decision tasks (Cornelissen et al, 1998b) or the detection of small letters (Stein and Walsh, 1997) for example. Since the earliest studies (Lovegrove et al, 1980(Lovegrove et al, , 1982(Lovegrove et al, , 1986) sinusgratings have been one of the most popular experimental means. Depending on the spatial frequency (cycles of the bright and dark bars per degree visual angle) dyslexics showed a reduced sensitivity (Evans et al, 1994;Kubová et al, 1995) for motion detection.…”
Section: Introductionmentioning
confidence: 99%